COMPARATIVE STUDY OF THE BUOYANCY BETWEEN MEN AND WOMEN (Fiep Bulletin - online, 2015)
During much time the idea that women floated more than men was claimed in the courses of scuba diving and leisure diving,  around of the world, lessons has been given without a clear understanding of the relation between the human body and its  buoyancy. Fontoura (2005) states that "in accordance with the refined data that there is not a probable relation  between the percentual of corporal fat or the corporal weight and the used amount of ballast in the independent diving" what means that the buoyancy is not  directly related to the percentual of fat or the corporeal weight. A comparative study between men and women and its buoyancy has been developed and it proved that it does not have a specific relation between the gender and the modification of the buoyancies.
Keywords: Diving; Buoyancy; Gendre